Características funcionais de implantes dentários: topografia superficial e molhabilidade - Barbosa, Tarsis Prado (2016)
Dental implants are subjected to different biosystems, so the biological performance of these components depends on the interaction between the implant material and the living system. Three surface characteristics of biomaterials used in the implants are regarded as relevant in the process of bone formation: chemical composition, surface energy and topography. In general, optimum performance of titanium implants is related to its passive oxide layer that mimics the bone ceramic nature. The surface roughness has influence on cell migration and proliferation and many studies show that implants with a rough surface have better bone apposition and bone-implant contact than implants with smooth surfaces. The surface free energy is related to wettability and may influence the level of implant interaction with the body. However, we still need a better understanding of this phenomenon and how it affects the surrounding biological environment. The objective of this study was to characterize the topography and the surface energy of two kinds of titanium implants and discs produced with the following treatments: double etching and double etching with nanometric hydroxyapatite deposition. To characterize the surface topography was used laser interferometry and SEM. A new method of using laser interferometry to measure the surface of dental implants with threaded interior angles larger than 70 ° is suggested. To characterize the discs surface energy, the dynamic and static sessile drop methods were used. Two new methods were proposed to characterize the surface energy of the implant itself: a qualitative method related to the phenomenon of capillarity and an immersion and emersion method of the implants in 3 different liquids. It was found in these implants types that the topography of the thread flanks (83% of the surface area that will be in contact with the living environment) can not be extrapolated through the topography of the discs. The results obtained in the characterization of the surface energy by the new methods proposed were consistent with the results obtained by the static and dynamic sessile drop methods. It was not observed free energy difference between the two implants studied.